Hitler & America - Fischer, Klaus P., 1942- (EBL-Schweitzer, 2011)
Historian Klaus P. Fischer seeks to understand more deeply how Hitler viewed America, the nation that was central to Germany's defeat. He reveals Hitler's split-minded image of America, consisting of two contrary mental representations: America and Amerika.